Exploring structural similarities between crystal phases using EBSD pattern comparison. Issue 7 (20th June 2014) - Nolze, G.; Winkelmann, A.
<x xml:space="preserve">Abstract</x> We discuss the application of EBSD for the analysis of structural features of magnetite and hematite relevant in the topotactic growth of both phases. The orientation relationships of both phases are investigated using characteristically related sets of Kikuchi patterns, which were collected from topotactically intergrown hematite variants and their parent magnetite crystal grain. We address the hexagonal description of trigonal and cubic phases with respect to crystallographic relationships. The combination of locally resolved EBSD measurements and microstructural investigations thus offers a promising opportunity to evaluate orientation relationships and intergrowth between magnetite and hematite.